Перехід іспанської преси до демократії (1976−1984 рр.) - Lazaruk, Yaryna; Лазарук, Ярина (Східноєвропейський національний університет ім. Лесі Українки, 2013)
В статті проаналізовано перехід, або транзицію, до демократії іспанської преси, починаючи з 1976 р., тобто від появи нових прогресивних видань, які забезпечували інформаційну підтримку демократичним перетворенням нового уряду Іспанії, та завершуючи 1984 р., коли відбулася приватизація державної преси через відкриті аукціони, тобто зникнення офіційного органу пропаганди держави.The article analyzes the transition to democracy of the Spanish press from the 1976 year of appearance of new progressive publication, which collaborated with the new government, to the 1984 year of privatization of state press through open auctions. The first period of the transition of the print media is characterized by the gradual transformation of the ideological press. Newspapers of the francoist party National Movement (Movimiento Nacional) become the property of the Autonomous Body of the Social Media Communications of the State (Organismo Autonomo Medios de Comunicacion Social del Estado). During the political transition to democracy the private newspapers of the new format appered in Spain marking the period of the commercial journalism.
The Transition to Democracy of the Spanish Press (1976−1984).
Keywords: друковані медіа; «паперовий парламент»; транзиція; приватизація державної преси; mass media; «paper parliament»; Transition; privatization of the state press